Effect of reaction time on the particle size of ZnO and ZnO : Ce obtained by a sol-gel method - Flor, J. (2004)
In this work particles of ZnO of size range 33-56 Angstrom were prepared by a sol-gel method. The effect of reaction time on the particle size of ZnO or ZnO:Ce was investigated by transmission electron microscopy measurements, UV-vis absorption and luminescence spectroscopy. A linear increase of the mean particle size is observed as a function of reaction time. The cerium-doped particles are bigger than the pure ZnO ones obtained at the same reaction time. A shift to lower energy at the maximum of the bands is observed in all absorption, emission and excitation spectra as a function of particle growth. From the absorption spectra the optical energy gap values (Eg) for these particles were determined. In the quantum size regime, Eg was found to decrease with particle growth.